Semiotika Riffaterre: Signifikansi Puisi Shirayuri Jima Karya Kaneko Misuzu - Mentari Nur Addinda Raharjo; Anak Agung Ayu Dian Andriyani; Ni Wayan Meidariani (Janaru Saja Jurnal Program Studi Sastra Jepang, 2023)
This article aims to determine the significance of the poem Shirayuri Jima by Kaneko Misuzu. The theory used in this research is Riffaterre's semiotic theory. Sources of data used in this study is primary data sources obtained from data collection using non-interactive methods. The data obtained were analyzed using a qualitative descriptive method, then presented with an informal method, namely the data is presented in the form of sentences that are good and can be understood easily. Based on the results of data analysis that has been obtained, it can be seen that the significance of Shirayuri Jima's poem is about someone with a closed personality who prefers to spend his time painting the imaginary world he creates.